The Influence of Instagram Social Media Marketing and Electronic Word of Mouth on Customer Decisions to Join R.A.Q Studio Gym Parung Panjang - Marsyanda Nuruz Zahra; Fadillah (Greenation Management and Business Review, 2026)
This study aims to analyze the influence of Instagram Social Media Marketing and Electronic Word of Mouth on Customer Decisions to join R.A.Q Studio Gym Parung Panjang. The research method used is quantitative with an associative approach. The research sample consisted of 91 respondents taken using simple random sampling technique. Data were analyzed using multiple linear regression, t-test, and F-test through IBM SPSS Statistics version 27 software. The results showed that all variables have a positive and significant influence. Partially, Instagram Social Media Marketing has a significant effect on Customer Decisions with t-count 10.337 > t-table 1.986. Electronic Word of Mouth also shows a positive and significant partial influence with t-count 15.823 > t-table 1.986. Simultaneously, both variables significantly influence customer decisions with F-count 125.104. The coefficient of determination (R Square) shows the contribution of independent variables of 74% in explaining Customer Decisions, while the remaining 26% is influenced by other factors. This proves that managing Instagram content and positive digital customer reviews is crucial in increasing interest in joining R.A.Q Studio Gym.